Determinants for oral hygiene and periodontal status among mentally disabled children and adolescents - Kumar S; Sharma J; Duraiswamy P; Kulkarni S (Wolters Kluwer Medknow Publications, 2009)
Aim: To assess the impact of socio-demographic and clinical variables on the oral hygiene and periodontal status in a sample of mentally disabled subjects. Materials and Methods: Study sample comprised of 171 mentally disabled subjects attending a special school in Udaipur, India. Oral hygiene status was assessed by Simplified Oral Hygiene Index (OHI-S) and periodontal status by Community Periodontal Index. Results: Stepwise linear regression analysis revealed that the best predictors in the descending order for oral hygiene index were disabled sibling, medical diagnosis, IQ level, education of mother and father. Having Down syndrome, less educated parents, poor economic status and a disabled sibling were the most important predictors for poor periodontal status. Conclusions: The present study highlighted that the oral hygiene and periodontal status of the present study population is poor and was influenced by medical diagnosis, IQ level, disabled sibling, parent′s level of education and economic status.